Diagnosis and therapy of pseudoexfoliation glaucoma - Jünemann, Anselm (Ophthalmologe, 2012)
Pseudoexfoliation (PEX) glaucoma is the most frequent and most important type of secondary glaucoma, accounting for approximately 25% of open angle glaucoma worldwide and currently representing the most common identifiable cause of glaucoma overall. Due to high intraocular pressure levels, marked diurnal pressure fluctuations and spikes, and rapid optic nerve damage and visual field loss, PEX glaucoma represents a relatively severe and progressive type of glaucoma. Therefore, hard and fast lowering of intraocular pressure is necessary. Fixed combinations in medical therapy and early glaucoma surgery are recommended. When considering a surgical procedure (e.g. selective laser trabeculoplasty, bleb-dependent or bleb-independent surgery) the timing of cataract surgery plays a major role. Pathogenesis, clinical characteristics and therapeutic aspects of PEX glaucoma are described in the following article.
EVALuna2:21092